Debian GNU/Linux Bible - Hunger, Steve (Hungry Minds, 2011)
Debian GNU/Linux is one of the major Linux distributions available today. It is known as the most open" of the Linux distributions -- for its commitment to the free software principals, and its community-centricism. It is also known for its tradition of high-quality packages and package management tools, as well as its focus on security issues. Debian GNU/Linux® Bible focuses on common apps, GUIs, networking, and system administration.